MAJOR ELEMENT ANALYSIS OF FINE TEPHRAS FOUND IN AN ICE CORE FROM DOME FUJI STATION, ANTARCTICA - コウノ, ミカ; フジイ, ヨシユキ; KOHNO, Mika; FUJII, Yoshiyuki (National Institute of Polar Research, 1999)
P(論文) Fine tephras from 25 visible tephra layers, which were found in an ice core from Dome Fuji Station in Dronning Maud Land in East Antarctica, were prepared for electron microprobe analyses. Major element compositions of the tephras in three layers at depths of 573,1361 and 2202m were determined by electron microprobe. The tephras in the 573 and 2202-m layers were andesite and dacite, respectively. These tephras were considered to be originated from Visokoi and Candlemas Islands in the South Sandwich Islands, respectively, on the basis of their chemical similarity to analyzed rocks from these sources. The 1361-m tephra having trachyte composition was considered to be originated from Mt. Takahe in Marie Byrd Land. These tephra layers may serve as key beds of Antarctic ice cores. departmental bulletin paper